Ancient Egyptian coffins : past, present, future - Strudwick, Helen; Dawson, Julie (Conservator) (Oxbow Books, 2019)
"This collection of papers by leading international experts on the subject of ancient Egyptian coffins, builds on a project based at the Fitzwilliam Museum, Cambridge, to study and record in detail its collection. Papers address a series of topics including: the development of coffins in antiquity, including iconographic and text-based studies, providing new insights into ancient Egyptian belief systems at different periods and regional differences in coffin presentation; the post-antiquity history of coffins, including their acquisition and subsequent treatment in museums around the world; developments in technical examination and methods of studying coffins, especially the use of multispectral imaging to provide non-invasive analysis of materials, and what this tells us about construction and decorative techniques at different periods and in response to the availability of different materials and increasing evidence of the re-use of materials and complete re-working of coffins for new owners, leading us to question fundamental attitudes to the purpose of coffins as a containers of human remains and the practices of craftsmen in the funerary industry. The papers stem from the conference Ancient Egyptian coffins: past, present, future, held at the Museum from April 7-9, 2016, to accompany the exhibition Death on the Nile: uncovering the afterlife of ancient Egypt"--